ASPEK HUKUM PERTANGGUNGJAWABAN KOMISARIS NOMINEE DALAM PERSEROAN TERBATAS ATAS TINDAK PIDANA YANG DILAKUKAN PERSEROAN - DENNY SALIM (PREMISE LAW JURNAL, 2016)
In the practice of corporation, a lot of nominee practices can be found in the organs of limited liability companies. Nominee Commissioner is used by the real owner of the company (beneficiary) in order to control the company freely—especially to the extent of the approval award for the Board of Directors’ (which might be Nominee Director as well) actions that need the approval from the Board of Commissioners—which is misused for committing crimes only for the sake of profit earning. This research is the research which uses the normative juridical or doctrinal legal study. The conclusions drawn from the result of this study are: the appointment of Nominee Commissioner is undertaken so that the real company owner (beneficiary) will be able to control the company freely without any concern of his/her name being appeared in the company documents dan could evade from legal liability if the Nominee Commissioner as the supervisory organ of the company did not perform his/her duties and obligations which resulted in the charges of legal sanctions; a Nominee Commissioner—given the reality that he/she is a mere fictitious commissioner organ who does not have any authorisation over the company—can always be charged of criminal liability towards the criminality (-ies) of the company by taking into the consideration of the mistake element inside himself/herself; and the charging of criminal liability towards both corporation and Nominee Commissioner altogether can only be carried out if the provisions have been regulated under certain prevailing laws. Keywords: Nominee Commssioner, Criminal Liability, Limited Liability Company